Strategies for Taming the City - Ndarova Audrey Kwangwama; Kadmiel H. Wekwete; Innocent Chirisa (Palgrave Macmillan, Cham, 2022)
The expansion of the urban areas into the peri-urban areas has now become a common phenomenon which characterizes most developments in both the developed and the developing worlds. Despite having the advantage of spreading economic activities into the periphery and creation of job opportunities for the residents, the encroachment of the city into its peripheral boundaries has been received with much scorn and negativity by many across the planning discourse as it has resulted in the eating away of the greenbelt, which has been linked to the birth of environmental challenges and food insecurities for the general populace. This has prompted most countries, especially in the developed countries, to put strategies in place, in order to control the growth of the city, for it not to result into urban sprawl and increased eating away of the surrounding land. This chapter is an insight into the experiences of the developing countries as regards managing the aspect of peri-urbanization, by also reflecting on the various strategies which are being employed by the developing world pertaining to taming the city.